Alloying effects and site occupancies of Re in the C14 Cr-based Laves phases: a first-principles study. Issue 32 (12th November 2018) - Zhang, Youjian; Zhang, Jianxin; Li, Pan; Jin, Huixin; Zhang, Wenyang; Ma, Shiyu
ABSTRACT: First-principles calculations based upon the density functional theory have been carried out to investigate the alloying effects and site occupancies of Re in the C14 XCr2 (X = Nb, Ta, Ti, Zr, Hf) Laves phases. The calculated results indicate that Re tends to facilitate and participate in the formation of the Laves phases, generating X8 Cr15 Re accordingly. The partial density of states and charge density diﬀerence were analysed to reﬂect the bonding characteristics. For X8 Cr15 Re, the bonding between the doped Re and its nearest neighbour Cr atoms all show covalent characteristics, which contribute to the phase stability. The substitution of Re on X sites is energetically unfavourable due to the weak bonding between Re and its nearest neighbour X atoms.